2020
DOI: 10.3389/fcell.2020.00215
|View full text |Cite
|
Sign up to set email alerts
|

GJB2 Mutations Linked to Hearing Loss Exhibit Differential Trafficking and Functional Defects as Revealed in Cochlear-Relevant Cells

Abstract: GJB2 gene (that encodes Cx26) mutations are causal of hearing loss highlighting the importance of Cx26-based channel signaling amongst the supporting cells in the organ of Corti. While the majority of these GJB2 mutations are inherited in an autosomal recessive manner, others are inherited in an autosomal dominant manner and lead to syndromic hearing loss as well as skin diseases. To assess if common or divergent mechanisms are at the root of GJB2-linked hearing loss, we expressed several mutants in cochlear-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 91 publications
(127 reference statements)
2
21
0
Order By: Relevance
“…Press et al (2017) revealed that S183F mutant has defects in connexin trafficking as well as impaired gap junction and hemichannel function and exhibited transdominant effects on co-expressed wild type Cx26, Cx30, and Cx43 [ 48 ]. Consistent with previous studies of this mutation, Beach et al [ 19 ] reported that the dominant syndromic S183F mutant was able to traffic to the plasma membrane (although some intracellular reservoirs of S183F were found) and to form gap junctions incapable of transferring a dye [ 48 , 70 ]. In addition, the S183F mutant co-localized in the same gap junctions as wild type Cx26 and Cx30, and gained a capacity to intermix with Cx43 within gap junctions [ 70 ].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Press et al (2017) revealed that S183F mutant has defects in connexin trafficking as well as impaired gap junction and hemichannel function and exhibited transdominant effects on co-expressed wild type Cx26, Cx30, and Cx43 [ 48 ]. Consistent with previous studies of this mutation, Beach et al [ 19 ] reported that the dominant syndromic S183F mutant was able to traffic to the plasma membrane (although some intracellular reservoirs of S183F were found) and to form gap junctions incapable of transferring a dye [ 48 , 70 ]. In addition, the S183F mutant co-localized in the same gap junctions as wild type Cx26 and Cx30, and gained a capacity to intermix with Cx43 within gap junctions [ 70 ].…”
Section: Discussionsupporting
confidence: 82%
“…Mani et al (2009) described defective localization of the R184P mutant protein found largely in the cytoplasm [ 40 ]. The results of Bruzzone et al (2003) in the paired Xenopus oocytes expression system, as well as of Beach et al (2020) in the cochlear-relevant HEI-OC1 cells, supported the R184P inability to form intercellular channels [ 19 , 28 ]. The recessive mutation p.C169Y previously classified as a polymorphism, has been identified as causative of severe hearing loss in two Qatari families.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Sensorineural HL (SNHL) is the most common form of HL and typically is caused by a loss of functional sensory hair cells (HCs) and supporting cells (SCs) within the cochlea [3,4]. HCs and SCs develop from common progenitor cells within the prosensory domain of the developing cochlea [5]. HCs transfer mechanical vibration into an acoustic electrical signal, which is then transmitted to the auditory cortex via spiral ganglion neurons (SGNs).…”
Section: Introductionmentioning
confidence: 99%